A 256-Kb Dual-VCC SRAM Building Block in 65-nm CMOS Process With Actively Clamped Sleep Transistor. - Khellah, M. (IEEE Journal of solid state circuits)
This paper addresses the stability problem of SRAM cells used in dense last level caches (LLCs). In order for the LLC not to limit the minimum voltage at which a processor core can run, a dual-VCC 256-Kb SRAM building block is proposed. A fixed high-voltage supply powers the cache which allows the use of the smallest SRAM cell for maximum density, while a separate variable supply is used by the core for ultra-low-voltage operation using dynamic voltage and frequency (DVF). Implemented in a 65-nm bulk CMOS process, the block features low overhead embedded level shifters and an actively clamped sleep transistor for maximum cache leakage power reduction during standby. Measured results show that the proposed block runs at 4.2GHz while consuming 30 mW at 85degC and 1.2V supply. Furthermore, measurements across a wide range of process, voltage, temperature, and aging conditions indicate virtual ground clamping accuracy within a few millivolts of required cache standby VMIN. Extrapolating the 256-Kb block measurement results in a large 64-Mb LLC used in a dual-V CC processor gives 35% reduction in total processor power as compared with a single-VCC processor design running at a high supply voltage